PENYAKIT BAWAAN : KAJIAN RESIKO KESEHATAN PADA PERKAWINAN SEPUPU - Yayuk Yusdiawati (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2017)
This paper aims to investige about congenital diseases are an absolute risk in all types of cousin marriages. Methods: This review is a review of literature on cousin marriages and congenital diseases in cousin marriages, as well as qualitative research conducted on the Mandailing community in the village of Tanjung Baringin, North Sumatra, which practices many cross-breed cousins. Result: the risk of the illness impacted by cousin marriage, is not an absolute negative impact on all cousin pairs. A parallel cousin has a great chance to experience it. This can be proved by some researchers who investige health risks in populations that practices parallel cousin marriage. In cross-cousin pairs did not find any health risks. Therefore, cousin marriage still exixtsnce until now, especially in cross cousin marriage.